New formula for the selection of the best competitor in the bench press - Haleczko, A.; Korzewa, L.; Misiolek, E. (Journal of Kinesiology and Exercise Sciences, 2016)
Introduction. This paper constitutes a continuation of research on score equalization in the bench press, and of the studies on athletes with disabilities conducted several years ago. In 2003, we presented score equalization coefficients in competitions under the IPC. These tables, designed for the period 2003-2007, are valid to this day. The current study is devoted to the construction of an efficient formula for healthy athletes and concerns the selection of the best competitor regardless of weight class. In weightlifting, such action is called score equalization. Material and methods. The collected material is comprised of the results of high-level competitors from the years 2011-2015, eight in each category. In creating the models, we used the three-variable formula validated in previous studies, requiring no adjustments in terms of the categories up to 84 and 120 kg. The obtained results are supplemented with calculations of Wilks coefficients. In terms of the heavy weight classes, the trend of decreasing performance with increasing body mass was adjusted. For the comparison of both formulas we used graphs, numerical data included in the coefficients of variation and differences between the world records after their conversion using both formulas. In addition, comparison indicating the effectiveness of equalization in three competitions of weightlifting is presented. Outstanding results in the middle-weight classes, and the weaker in the extremes categories, should be explained by the normal distribution of body mass typical of the population, although some authors believe that this is the result of allometric scaling. Conclusions. The New Formula, being much more effective in score equalization, can successfully replace the outdated Wilks tables.